2015
DOI: 10.1080/09168451.2014.991683
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid binds to peroxisome proliferator-activated receptor γ and promotes adipocyte differentiation in 3T3-L1 adipocytes

Abstract: We examined the effect of perfluorooctanoic acid (PFOA) on adipose cells using 3T3-L1 adipocytes and found that PFOA increased adipocyte differentiation, triglyceride accumulation, and the mRNA level of factors related to adipocyte differentiation. In addition, PFOA bound to peroxisome proliferator-activated receptor γ (PPAR γ). These results suggest that PFOA promotes adipocyte differentiation as a PPAR γ ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 21 publications
(25 reference statements)
2
24
0
Order By: Relevance
“…Regarding adipogenesis, the nuclear peroxisome proliferator-activated receptor gamma (PPAR-gamma) is an ultimate promoter of adipogenesis and hinders both osteoblastogenesis and myogenesis. The PPAR-gamma is also involved in adipocyte maturation and metabolism [63][64][65].…”
Section: Key Cellular and Endocrine Interactions Among Bone Muscle mentioning
confidence: 99%
“…Regarding adipogenesis, the nuclear peroxisome proliferator-activated receptor gamma (PPAR-gamma) is an ultimate promoter of adipogenesis and hinders both osteoblastogenesis and myogenesis. The PPAR-gamma is also involved in adipocyte maturation and metabolism [63][64][65].…”
Section: Key Cellular and Endocrine Interactions Among Bone Muscle mentioning
confidence: 99%
“…PCB metabolites are high-affinity ligands for the thyroid hormone transport protein transthyretin (Cheek et al, 1999). p,p'-DDE binds to the androgen receptor (Kelce et al, 1995;Xu et al, 2013), while PFOA promotes adipocyte differentiation as a peroxisome proliferator-activated receptor gamma (PPARγ) ligand (White et al, 2011;Yamamoto et al, 2015). Several studies in rats demonstrated the thyroid-disrupting effect of the pesticides DDT (Scollon et al, 2004) and HCB (Alvarez et al, 2005;van Raaij et al, 1993a;van Raaij et al, 1993b), as they decreased serum levels of thyroid hormones.…”
Section: Mechanismsmentioning
confidence: 99%
“…Perfluorinated alkylic acids (PFAAs) are documented to bind to and/or interact with many proteins, potentially interfering with their normal physiological function. This includes serum albumin (SA) that acts as blood fatty acid transporter system [9], and proteins highly expressed in the liver, such as liver fatty acid binding protein (L-FABP) that is responsible for fatty acid uptake, transport and metabolism [10] and peroxime proliferated-activated receptors alpha and gamma (PPARα and PPARγ) [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%